Necessary and sufficient conditions for the oscillation of solutions of nonlinear differential equations with pulse influence in a banach space - Slyusarchuk, V. E. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We obtain necessary and sufficient conditions for the oscillation of solutions of nonlinear second-order differential equations with pulse influence in a Banach space.